Sublime Communion and the Costs of Evolution - Edwards, Denis 1943-2019 (2019)
Both the crisis of life on our planet and major developments in the sciences demand a rethinking of the theological understanding of the human in relationship to the rest of the natural world. Since Pope Francis's theology of sublime communion provides an important resource for this work, the first section of the article analyses what is said of this communion in Laudato Si'. In the second section, a critical theological issue is raised, one not dealt with in the encyclical, concerning the costs of evolution: the pain, predation, violence, death, and extinction built into the natural world. In the last two sections, it is proposed that the word sublime that Pope Francis uses is capable of embracing the harsh side of creation, through a brief survey of the distinction between beauty and the sublime in philosophical aesthetics, and then through an exploration of the use of the word sublime in the mystical theology of John of the Cross.
Keywords: John of the Cross; Pope Francis; Communion; costs of evolution; philosophical aesthetics; Sublime